THE IMPACT OF US-CHINA TRADE WAR ON INVESMENT DECISION IN INDONESIA - Djuandi, Jacqueline Valentine; Hartono, Wendra (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
The US–China trade war has created substantial uncertainty in the global economy, influencing investment patterns in emerging markets such as Indonesia. This study examines how financial literacy, risk perception, and locus of control shape Indonesian investors’ decisions when choosing between risky and safe assets during this period of economic volatility. By focusing on behavior displayed throughout the trade war, the research highlights how investors weigh potential risks against expected returns amid heightened market instability. Using a quantitative approach, the study employs multiple regression analysis to assess the extent to which these psychological and economic factors affect investment choices. The findings aim to deepen the understanding of investor behavior in times of crisis and provide practical insights for both individual and institutional investors navigating uncertain conditions. Furthermore, the results contribute to the broader field of behavioral finance by illustrating how cognitive and psychological traits influence investment strategies. Insights from this study may assist policymakers, financial advisors, and investors in developing more informed approaches to managing portfolios during periods of global economic disruption.